Cerebral regional oxygen saturation trends in infants with hypoxic-ischemic encephalopathy. (October 2017) - Jain, Siddharth V.; Pagano, Lindsay; Gillam-Krakauer, Maria; Slaughter, James C.; Pruthi, Sumit; Engelhardt, Barbara
Abstract: Background: Neurological outcomes in neonatal hypoxic-ischemic encephalopathy (HIE) continue to be sub-optimal despite therapeutic hypothermia (TH). Cerebral near-infrared spectroscopy provides real-time regional oxygen saturation (CrSO2 ) that may be a marker of adverse MRI findings and neurodevelopmental outcomes. Aim: The aim of this study was to examine the value of CrSO2 monitoring in infants with HIE undergoing TH. Study design and subjects: In this prospective study, CrSO2 was continuously recorded in 21 infants with HIE admitted for TH. Outcome measures: Brain MRI signal abnormalities at 2 weeks were scored in individual brain region and classified as none/mild, moderate and severe. 13 infants completed Bayley Scales of Infant Development (BSID) testing at 18–24 months. Results: Between 24 and 36 h of life, there was a significant increase in odds of having moderate-severe brain MRI abnormalities with higher absolute CrSO2 values. Per 10% increase in absolute CrSO2, the odds ratio for moderate-severe brain MRI abnormalities was greatest at 30 h (OR 3.78; confidence intervals (CI): 1.23–11.6, p = 0.011). CrSO2 increased more rapidly in infants with greater injury seen on MRI (0.20/h for MRI scores 0/1, by 0.48/h for MRI score 2, and by 0.68/h for MRI score 3, p = 0.05). At 30 h, absolute CrSO2 correlated significantly with abnormal MRI findings in basal ganglia (92% vs. 78%, p = 0.001), white matter (88% vs. 76%, p = 0.01), posterior limb of internal capsule (92% vs. 78%, p = 0.001), and brain stem (94% vs. 80%, p = 0.03) but not with cortical injury (86% vs. 80%, p = 0.17). Higher CrSO2 beyond 24 h correlated with greater odds of worse BSID scores. Conclusions: Increasing CrSO2 is associated with moderate-severe brain injury as assessed by MRI. Higher absolute CrSO2 values during TH correlates with subcortical injury on MRI and poor neurodevelopmental outcomes in infants with HIE undergoing TH. CrSO2 can inform providers seeking early identification of patients at risk of worse injury who may benefit from further intervention. Highlights: Encephalopathic infants with moderate to severe MRI injury have a rapid rise of CrSO2 in the first 36 h. Infants with moderate to severe MRI injury and poor neurodevelopmental outcome have higher CrSO2 beyond 24 h of life. NIRS could be useful to follow cerebral hemodynamic response to therapeutic hypothermia. NIRS measured in bi-frontal head region is a practical technology possibly indicating subcortical injury in neonatal HIE.